Endoscopic Band Ligation Versus Pharmacological Therapy for Variceal Bleeding in Cirrhosis: A Meta-Analysis - Lan Li; Chaohui Yu; Youming Li (Canadian Journal of Gastroenterology)
OBJECTIVE: To conduct a meta-analysis of published, full-length, randomized controlled trials evaluating the efficacy of endoscopic band ligation (EBL) versus pharmacological therapy for the primary and secondary prophylaxis of variceal hemorrhage in patients with cirrhosis.